Advances in biogenically synthesized shaped metal- and carbon-based nanoarchitectures and their medicinal applications - Zare, Ehsan Nazarzadeh; Padil, Vinod V T; Mokhtari, Babak; Venkateshaiah, Abhilash; Wacławek, Stanislaw; Černík, Miroslav; Tay, Franklin R; Varma, Rajender S; Makvandi, Pooyan (Advances in colloid and interface science, 2020)
Non-spherical metal-based and carbon-based nanostructures have found applications in every facet of scientific endeavors, including engineering and biomedical fields. These nanostructures attract attention because of their biocompatibility and negligible cytotoxicity. Chemical and physical methods have been used for synthesizing earlier generations of metal-based and carbon-based nanostructures with variable architectures, including nanorods, nanowires, nanodots and nanosheets. However, these synthesis strategies utilize organic passivators which are toxic to the environment and the human body. Biogenic synthesis of nanoparticles is becoming increasing popular because of the necessity to develop eco-friendly and non-toxic strategies. Nanoparticles synthesized by natural compounds have immense potential in the biomedical arena. The present review focuses on plant-mediated synthesis of metal-based and carbon-based non-spherical nanoarchitectures and the role of green synthesis in improving their activities for biomedical applications.
Keywords: nanostruktury; Metals; Nanotechnology; Biocompatible Materials; lidé; nanotechnologie; Nanostructures; Carbon; uhlík; biokompatibilní materiály; kovy; Humans